Proposal for Data Retrieval Methodology in Terms of Cross-border Commuter Mobility: A Perspective of Czech Employees - Ľupták, Vladimír; Stopka, Ondrej; Hanzl, Jiří; Kampf, Rudolf; Gross, Patrik; Scholze, Dominic; Martens, Maren (Periodica polytechnica. Transportation engineering, 2025)
Labor mobility between the Czech Republic and Germany represents a significant factor for the economic and social integration of cross-border regions. The manuscript focuses on the proposal of a methodology in the context of retrieving and analyzing data on labor mobility, with the aim of creating a strategy to support cross-border cooperation. Through a combination of specific quantitative and qualitative methods, the manuscript analyzes the key determinants of mobility, barriers, challenges and factors affecting the commuter decision-making. The findings show that the major obstacles to cross-border mobility include administrative burden, differences in working conditions, and institutional misalignment. The manuscript also discusses the possibility of optimizing the current data retrieval system using advanced technologies and analytical tools. The conclusions of the study provide suggestions for streamlining cross-border mobility and supporting labor market integration in the Czech-German border region.